Factors affecting adoption of major adaptation strategies against drought among summer vegetables growers in central Nepal - Subedi, A. P.; Dangol, D. R.; Dhakal, S. C; Tiwari, U. (Journal of Agriculture and Forestry University, 2022)
Climate change is one of the critical challenges in the field of agriculture and drought is one among the important effects of global climate change affecting summer vegetables in central Nepal. A research was conducted in central Nepal to seek out factors affecting adaptation strategies against drought among summer vegetables growers. A semi-structured questionnaire was used to collect primary data from 300 households adjoining Trishuli Narayani River corridor equally divided among three districts namely Chitwan, Dhading and Nuwakot. Data obtained were analyzed using descriptive statistic and logit model. Irrigation canal, choosing appropriate crop varieties, mulching, adjusting planting time and using organic manure were identified important adaptation strategies for drought within the study areas. Distance of vegetable farm from river, knowledge of climate change with the respondents, training provided to farmers on vegetable farming, access to cooperative was seen significantly affecting farmers to settle on those adaptation strategies against drought. Adopting different practices against drought found to be correlated with topography or agro climatic regions as well. Nuwakot and Dhading with high altitude got less chance of using organic manure and mulching practice in comparison with Chitwan but its opposite with other adaptation practices like adjusting planting times, changing crop varieties and using irrigation canal. Policy makers and extension workers should focus more on knowledge input based on topography or agroclimatic regions as well about climate change adaptation practices among the farmers, hence providing more trainings on vegetable farming, increasing the access to cooperatives and other organizations could ultimately help to strengthen vegetable growers to adopt those adaptation practices.